2015
DOI: 10.1042/cs20140832
|View full text |Cite
|
Sign up to set email alerts
|

Circulating PCSK9 levels are positively correlated with NMR-assessed atherogenic dyslipidaemia in patients with high cardiovascular risk

Abstract: The proprotein convertase subtilisin/kexin type 9 (PCSK9) gene regulates cholesterol homoeostasis by accelerating low-density lipoprotein receptor (LDLR) degradation resulting in the decreased catabolism of low-density lipoprotein (LDL) leading to hypercholesterolaemia. PCSK9 has also been related to other metabolic risk factors such as triglycerides (TGs) and glucose levels and body mass index (BMI). Therefore, our aim was to study the relationship between the PCSK9 and the lipid and lipoprotein profile. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 40 publications
(34 reference statements)
5
22
0
Order By: Relevance
“…[9][10][11][12][13][34][35][36] Other possible explanations for the effect of PCSK9 on CVD involve its impact on atherogenic lipoproteins independently of its impact on the LDLR pathway. Guardiola et al 16 recently reported that circulating PCSK9 levels were positively correlated with large very-low-density lipoprotein and their remnants, intermediate-density…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…[9][10][11][12][13][34][35][36] Other possible explanations for the effect of PCSK9 on CVD involve its impact on atherogenic lipoproteins independently of its impact on the LDLR pathway. Guardiola et al 16 recently reported that circulating PCSK9 levels were positively correlated with large very-low-density lipoprotein and their remnants, intermediate-density…”
Section: Discussionmentioning
confidence: 97%
“…Other possible explanations for the effect of PCSK9 on CVD involve its impact on atherogenic lipoproteins independently of its impact on the LDLR pathway. Guardiola et al recently reported that circulating PCSK9 levels were positively correlated with large very‐low‐density lipoprotein and their remnants, intermediate‐density lipoprotein particles known for their potent atherogenicity. In addition, PCSK9 was correlated with smaller LDL particles as well as with HDL particles, mainly explained by the correlation between PCSK9 and the smallest HDL particles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, plasma PCSK9 levels positively associate with fasting plasma TG levels in adults and adolescents in the general population, and also in patients with T1DM and T2DM . Specifically, plasma PCSK9 levels associate with (large) VLDLs, VLDL remnants and intermediate‐density lipoproteins (IDLs) in subjects with T2DM and/or metabolic syndrome . Genetic studies have also demonstrated that specific gain‐of‐function variants (notably p.S127R and p.D374Y) modestly increase plasma TG levels, whereas certain loss‐of‐function variants (p.Y142X, p.C679X, p.R46L) modestly lower plasma TG levels .…”
Section: Pcsk9 and Diabetesmentioning
confidence: 99%
“…28 Specifically, plasma PCSK9 levels associate with (large) VLDLs, VLDL remnants and intermediatedensity lipoproteins (IDLs) in subjects with T2DM and/or metabolic syndrome. 44 Genetic studies have also demonstrated that specific gain-of-function variants (notably p.S127R and p.D374Y) modestly increase plasma TG levels, 45,46 whereas certain loss-of-function variants (p.Y142X, p.C679X, p.R46L) modestly lower plasma TG levels. 17,47,48 One potential explanation for the positive relationship between plasma TG and plasma PCSK9 levels is an intracellular effect of PCSK9 on APOB/VLDL secretion.…”
Section: Pcsk9 and Diabetesmentioning
confidence: 99%